A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

Model based random packing optimisation for absorption processes using the hydrodynamic analogy concept - Salten, Alexander Heinrich Johannes; Kenig, Eugeny (Chemical Engineering Science)

Investigation of the pressure-throughput behavior of different faceted mixer geometries on an analytical and simulative basis - Frank, Maximilian; Hollenhorst, Viola; Schöppner, Volker (36th International Conference of the Polymer Processing - PPS 2021)

Development of a Dynamic Modeling Approach to Simulate a Segmented Distillation Column for Flexible Operation - Bruns, Bastian; Fasel, Henrik; Grünewald, Marcus; Riese, Julia (ChemEngineering)
The need for flexible process equipment has increased over the past decade in the chemical industry. However, process equipment such as distillation columns have limitations that significantly restrict flexible operation. We investigate a segmented tray column designed to allow flexible operation. The design consists of radial trays connected at the downcomer of each tray. Each segment can be operated separately, but depending on the capacity of the feed stream, additional segments can be activated or deactivated. The connection between the trays aims to transfer liquid from one stationary segment to the adjacent inactive segment, thereby reducing the time required for the start-up process. In a case study on the separation of methanol and water, we perform dynamic simulations to assess the reduction in the start-up time of inactive segments. The results confirm the advantages over standard tray designs. The segmented distillation column is a step towards improving the flexibility of separation operations.
Keywords: General Energy; General Engineering; General Chemical Engineering

Concept of a Flexible Wetted‐Wall Column for the Distillation of Specialty Chemicals - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Chemical Engineering & Technology)
Abstract The trend of increasing product diversity and decreasing production amounts led to the requirement of higher flexibility of production processes of specialty chemicals. Conventional distillation columns, mostly equipped with structured packings, lack the flexibility to handle product changeovers and throughput. Thus, a newly designed distillation column for specialty chemicals is presented. A numerical model was implemented to analyze the potential of the wetted‐wall column. The simulation of the distillation of a binary methanol/water mixture demonstrated that the wetted‐wall column can generate the desired concentration and temperature profiles. Furthermore, analyses of the pressure drop and separation efficiency with the test system chlorobenzene/ethylbenzene were conducted.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Characterization of Liquid-Phase Distribution in 3D Printed Structured Packings with an Enclosed Column Wall - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Flexibility analysis for demand-side management in large-scale chemical processes: An ethylene oxide production case study - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Indirect Demand Response Potential of Large-Scale Chemical Processes - Bruns, Bastian; Di Pretoro, Alessandro; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Dynamic Design Optimization for Flexible Process Equipment - Bruns, Bastian; Herrmann, Felix; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Efficient Production of Specialized Polymers with Highly Flexible Small‐Scale Plants - Bruns, Bastian; Becker, Tristan; Riese, Julia; Lier, Stefan; Werners, Brigitte (Chemical Engineering & Technology)
Abstract Shortened product life cycles and increased demand for specialized products lead to more challenges in efficiently satisfying customer needs. Customer demands are increasingly uncertain in terms of type, location, and volume. As a result, more flexible chemical production plants are required. Modular small‐scale plants can be installed in transportation containers and, therefore, offer the flexibility of easy relocation, enabling production close to the customer or supplier. In a mathematical optimization model, the economic benefit of small‐scale plants in the specialty chemicals market of polymer production is analyzed. Different scenarios created from the real data of a chemical company show that the use of small‐scale plants may lead to a significant reduction in total costs that is mainly due to the transportation costs of raw materials and products.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Experimentelle Untersuchungen zum Tropfenmitriss im Feedeinleitbereich von Destillationskolonnen - Fasel, Henrik; Darvishsefat, Novin; Riese, Julia; Grünewald, Marcus (Chemie Ingenieur Technik)
Abstract Im Rahmen dieses Beitrags werden experimentelle Untersuchungen zur Tropfenabscheidung im Einleitbereich eines Stoffaustauschapparates für zweiphasige Strömungen vorgestellt. Dafür wurde in einem Versuchsstand im Pilotmaßstab der qualitative Tropfenmitriss für unterschiedliche Tropfenabscheider eines Stoffaustauschapparates vermessen. Die daraus resultierenden Ergebnisse werden in diesem Beitrag hinsichtlich ihrer Aussagekraft zur Vermeidung von Tropfenmitriss diskutiert und bewertet. Darüber hinaus wird ein kurzer Ausblick über simulative Arbeiten zur Bestimmung des Tropfenmitriss gegeben.
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Heat transfer enhancement within internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Sheet Metal 2021)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Tribology; Sheet Metal; Simulation

"Lobe den Herren, den mächtigen König der Ehren" - Ein Lied mit Lebensbezug - Breckner, Anne (Musik als Lebensmittel: Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Conference Report: Dynamics of Tradition: Islamic Theology and Law in Relation (September 17-19, 2021, Paderborn) - Nassery, Idris; Tatari, Muna; Mustafa, Abdul Rahman

Our Energy Grids as Enabler for More Sustainability. Talk - Schlüter, Alexander

Wir müssen handeln: Jetzt! - Schlüter, Alexander; Bernabé-Moreno, Juan (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Wer grüne Energie will, muss auch koppeln und speichern - Meschede, Henning; Khripko, Diana; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities and Smart Rural Areas)

Insights into the Future Energy System in Smart Cities and Rural Areas. Talk - Schlüter, Alexander

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)

Optimization of packed bed latent heat storages filled with PCM-capsules based on super-ellipsoids - Grabo, Matti; Kuckuck, Lennart; Kenig, Eugeny

Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan Yuksel; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Feasibility study of a new static-mechanical rounding of polymer particles for selective laser sintering (Studienarbeit) - Bommidi, Karthik; Ponusamy, SathishKumar

Energie einsparen in Industrie und Gewerbe - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Mit Energieeffizienz Grundlagen legen - Hechelmann, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Der Prosumer im Zentrum des digitalen Energiesystems - Ikonnikova, Svetlana; Schlüter, Alexander; Brandner, Bernadette (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Energieeffiziente Gebäude - Emmerich-Bundel, Garance; Lindauer, Manuel; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Die smarte Kommune in Stadt und Land - Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Digitale Transformation aus der Perspektive von Kindern und Jugendlichen in Europa gestalten – das Horizon-Projekt DigiGen. PlanBD #4 Around the World - Eickelmann, Birgit; Drossel, Kerstin; Casamassima, Gianna; Labusch, Amelie (Fachmagazin für Schule in der digitalen Welt)

The younger generation’s views on how their education is preparing them for the digital age against the background of COVID-19 - Eickelmann, Birgit; Barbovschi, Monica; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, Greta Björk; Holmarsdottir, Halla Bjork; Kazani, Aggeliki; Mifsud, Louise; Parsanoglou, Dimitris; Port, Sonja; Sisask, Merike; Symeonaki, Maria; et al.

Digital diversity across Europe. Policy brief September 2021 of Working Package 2 'Mapping digital transformations across Europe' in Horizon-2020-Project DigiGen - Ayllón, Sara; Casamassima, Gianna; Drossel, Kerstin; Eickelmann, Birgit; Hyggen, Christer; Lado, Samuel; Port, Sonja; Broekstra, Nienke

Noticing im naturwissenschaftlichen Sachunterricht der Grundschule - Gövert, Andre (Sprachtheorien in der Zweit- und Fremdsprachenforschung. Eine Basis für empirisches Arbeiten zwischen Fach- und Sprachlernen.)

Digitale Prozessintegration in berufs- und wirtschaftspädagogischen Studiengängen – Überlegungen zur Professionalität und professionellen Entwicklung - Jenert, Tobias; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik – online)

Being a first-year student during COVID-19 pandemic - Büker, Ronja (Zeitschrift für Hochschulentwicklung)

Anderssein als Ressource: Habitus und Habitusreflexion in der Lehrer*innenbildung - Jenert, Tobias (PraxisForschungLehrer*innenbildung)
Lehrer*innen können dazu beitragen, dass bestehende soziale Ungleichheiten verstärkt oder auch abgebaut werden. Eine wichtige Rolle spielen dabei der sogenannte Habitus der Lehrer*innen und dessen (Nicht-)Passung zur sozialen Herkunft der Schüler*innen. In diesem Text stelle ich die Frage, wie angehende Lehrer*innen im Studium unterstützt werden können, die Bedeutung eigener habitueller Prägungen für das professionelle Handeln als Lehrperson zu reflektieren. Ganz besonders befasse ich mich mit der Rolle der Lehrer*innenbildner*innen bei der Förderung von solchen habitusreflexiven Kompetenzen. Hier spielen das Selbst der Hochschullehrenden und die bildungsbiographischen Erfahrungen, die auf dem Weg in die Hochschule gemacht wurden, eine wichtige Rolle.

Digitale Prozessintegration in der beruflichen Lehrer*innenbildung – Praxisnahe Einblicke in die Entwicklung des wirtschaftspädagogischen Studienangebots an der Universität Paderborn - Sänger, Niklas

Einblicke in die curriculare Entwicklung des wirtschaftspädagogischen Studienangebots mit Hilfe der Fallstudiendidaktik - Sänger, Niklas

Soziale Netzwerke als Treiber und Qualitätsmerkmal einer lehrbezogenen Hochschulentwicklung - Sänger, Niklas; Jenert, Tobias

Bausteine der didaktischen Fallstudienentwicklung für die beruflichen Lehrer*innenbildung im Projekt DiPoLe - Sänger, Niklas

Lehrentwicklungs-Netzwerke und institutionelle Ideen der Hochschullehre - Sänger, Niklas; Jenert, Tobias

Lehrentwicklung an Hochschulen als transferorientierte Netzwerkarbeit: Das Bündnis für Hochschullehre Lehren - Jenert, Tobias; Bosse, Elke (Transfer von Innovation und Wissen)

From entrepreneurial experience to expertise: A self-regulated learning perspective - Winkler, Christoph; Fust, Alexander; Jenert, Tobias (Journal of Small Business Management)
Keywords: Management of Technology and Innovation; Strategy and Management; General Business; Management and Accounting

Gestaltung von Studienangeboten. Konzepte, Modelle, Perspektiven - Jenert, Tobias (Handbuch Hochschuldidaktik)

The interplay of personal and contextual diversity during the first year at Higher Education: Combining a quantitative and a qualitative approach - Jenert, Tobias; Brahm, Taiga (Frontline Learning Research)
Research on student transition into Higher Education (HE) has taken different theoretical perspectives. First, studies investigated personal variables such as students´ self-efficacy, emotions and motivation regarding the transition from school to HE. A second strand of research focused on contextual variables, for instance college effectiveness research. With this paper, we combine both the personal and the contextual approach. We aim to investigate the interaction between personal and contextual diversity during the transition into HE, taking into account students’ diversity in particular with regard to gender and individual characteristics, such as self-efficacy. We explored the heterogeneity in students’ personal characteristics by conducting a latent profile analysis (LPA) based on students’ intrinsic motivation, self-efficacy and anxiety before entering Higher Education. LPA resulted in three distinct profiles, with significant differences in how students perceived the first year. This finding suggests that students’ personal characteristics when entering Higher Education influence how they experience the study environment. To investigate the interplay between individual and contextual differences in more detail, we conducted a qualitative longitudinal study with 14 first-year students in parallel with the panel survey. We found that individual students react very differently to specific characteristics and events of the first-year environment. Our study adds to the growing body of research that aims to grasp the complexity of interactions between individual and contextual differences. Specifically, we illustrate how combining quantitative and qualitative methods can provide new insights into person-context interactions.
Keywords: Education

Curriculumforschung - Jenert, Tobias (Handbuch TransdisziplinÃ¤re Didaktik)

Stolpersteine Osnabrück. Projektmaterial für Grundschule und Sekundarstufe I - Becher, Andrea; Grewe, Christine

Counter Model Transformation for Explaining Non-Subsumption in EL - Alrabbaa, Christian; Hieke, Willi; Turhan, Anni-Yasmin (Proceedings of the 7th Workshop on Formal and Cognitive Reasoning co-located with the 44th German Conference on Artificial Intelligence {(KI} 2021), September 28, 2021)

Answering Regular Path Queries Under Approximate Semantics in Lightweight Description Logics - Gil, Oliver Fernández; Turhan, Anni-Yasmin (Thirty-Fifth AAAI Conference on Artificial Intelligence, AAAI 2021, Thirty-Third Conference on Innovative Applications of Artificial Intelligence, IAAI 2021, The Eleventh Symposium on Educational Advances in Artificial Intelligence, EAAI 2021, Virtual Event, February 2-9, 2021)

Enhancing Probabilistic Model Checking with Ontologies - Dubslaff, Clemens; Koopmann, Patrick; Turhan, Anni-Yasmin (Formal Aspects Comput.)

Efficient TBox Reasoning with Value Restrictions using the \(\mathscrF\)\(\mathscrL\)\(_\mbox0\)wer reasoner - Baader, Franz; Koopmann, Patrick; Michel, Friedrich; Turhan, Anni-Yasmin; Zarrieß, Benjamin (CoRR)

Development of a Method to Derive Design Guidelines for Production-suitable Support Structures in Metal Laser Powder Bed Fusion - Lammers, Stefan; Lieneke, Tobias; Zimmer, Detmar

Dimethyl ether (DME) and dimethoxymethane (DMM) as reaction enhancers for methane: Combining flame experiments with model-assisted exploration of a polygeneration process - Zhang, Hao; Kaczmarek, Dennis; Rudolph, Charlotte; Schmitt, Steffen; Gaiser, Nina; Oßwald, Patrick; Bierkandt, Thomas; Kasper, Tina; Atakan, Burak; Kohse-Höinghaus, Katharina (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Oxidation of oxymethylene ether (OME0−5): An experimental systematic study by mass spectrometry and photoelectron photoion coincidence spectroscopy - Gaiser, Nina; Bierkandt, Thomas; Oßwald, Patrick; Zinsmeister, Julia; Kathrotia, Trupti; Shaqiri, Shkelqim; Hemberger, Patrick; Kasper, Tina; Aigner, Manfred; Köhler, Markus (Fuel)
Keywords: Organic Chemistry; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering

Photoelectron Photoion Coincidence Spectroscopy Provides Mechanistic Insights in Fuel Synthesis and Conversion - Hemberger, Patrick; Bodi, Andras; Bierkandt, Thomas; Köhler, Markus; Kaczmarek, Dennis; Kasper, Tina (Energy & Fuels)
Keywords: Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering

Ein modellbasiertes Messverfahren zur Charakterisierung von Piezokeramiken unter Verwendung eines einzelnen scheibenförmigen Probekörpers - Feldmann, Nadine
Designprozesse von Schallwandlern werden durch zunehmende Rechenkapazitäten immer mehr durch simulative Betrachtungen unterstützt. Dabei ist vor allem die Wahl der Materialparameter der verwendeten Materialien wichtig für ein realitätsnahes Simulationsergebnis. Bei Schallwandlern werden häufig Piezokeramiken als aktive Elemente genutzt, welche sich durch eine Verkopplung mechanischer und elektrischer Eigenschaften auszeichnen. Zur Bestimmung ihrer Materialparameter stellt der IEEE Standard on Piezoelectricity ein standardisiertes Verfahren dar. Dazu sind fünf Impedanzmessungen an vier unterschiedlich gefertigten Probekörpergeometrien notwendig. Da an jedem einzelnen Probekörper nur eine Untermenge aller notwendigen Materialparameter bestimmt werden kann, werden diese dann zu einem kompletten Materialparametersatz zusammengefügt. Aufgrund der unterschiedlichen Prozessbedingungen, bei denen die jeweiligen Probekörper hergestellt werden, ist dieser Materialparametersatz jedoch inkonsistent und kann nie das Verhalten einer einzelnen Probe beschreiben. Daher wird in der vorliegenden Arbeit ein Messverfahren entwickelt, mit dem es möglich ist, alle relevanten Materialparameter unter besonderer Berücksichtigung von Dämpfung an einem einzelnen Probekörper allein durch Impedanzmessungen zu bestimmen. Als Probekörper wird dazu eine in der Anwendung häufig verwendete Scheibengeometrie verwendet. Um eine hinreichend hohe Sensitivität auf alle Materialparameter zu gewährleisten, wird diese mit einer optimierten Elektrodentopologie gefertigt. Da in diesem Fall keine analytische Betrachtung mehr möglich ist, wird das Messverfahren durch einen inversen Ansatz realisiert.

Using data cards for teaching data based decision trees in middle school - Podworny, Susanne; Fleischer, Yannik; Hüsing, Sven; Biehler, Rolf; Frischemeier, Daniel; Höper, Lukas; Schulte, Carsten (Proceedings of the 21st Koli Calling International Conference on Computing Education Research)

Women in Global Health Germany - für mehr Chancengleichheit in der globalen Gesundheit. - Hoffmann, Christina; Schneider, Tamara; Kickbusch, Ilona; Ludwig, Sabine

Ensuring User Interface Adaptation Consistency through Triple Graph Grammers - Biermeier, Kai; Yigitbas, Enes; Weidmann, Nils; Engels, Gregor (Proceedings of the International Workshop on Human-Centered Software Engineering for Changing Contexts of Use)

"Schwangerschaft ressourcenorientiert erleben" (SRE-Studie) - Das Zürcher Ressourcen Modell (ZRM) als Intervention zur Stressreduktion in der Geburtsvorbereitung. - Schneider, Tamara

Entwicklungssystematik zur Integration von Eigenschaften der Selbstheilung in Intelligente Technische Systeme - Hillebrand, Michael

Ultrabreitbandige Sampler in SiGe-BiCMOS-Technologie für Analog-Digital-Wandler mit zeitversetzter Abtastung - Wu, Liang

„Zunge: Sprache“ Literarische Mehrsprachigkeit im Deutschunterricht am Beispiel der Erzählung „Mutterzunge“ von Emine Sevgi Özdamar - Büttner, Denise; Roll , Heike (Vermitteln - verbinden - verstehen. 46. Jahrestagung des Fachverbandes Deutsch als Fremd- und Zweitsprache an der Technischen Universität Chemnitz)

A convergent finite element algorithm for mean curvature flow in higher codimension - Binz, Tim; Kovács, Balázs (arXiv)

A convergent finite element algorithm for generalized mean curvature flows of closed surfaces - Binz, Tim; Kovács, Balázs (IMA Journal of Numerical Analysis)
Abstract An algorithm is proposed for generalized mean curvature flow of closed two-dimensional surfaces, which include inverse mean curvature flow and powers of mean and inverse mean curvature flow. Error estimates are proved for semidiscretizations and full discretizations for the generalized flow. The algorithm proposed and studied here combines evolving surface finite elements, whose nodes determine the discrete surface, and linearly implicit backward difference formulae for time integration. The numerical method is based on a system coupling the surface evolution to nonlinear second-order parabolic evolution equations for the normal velocity and normal vector. A convergence proof is presented in the case of finite elements of polynomial degree at least 2 and backward difference formulae of orders 2 to 5. The error analysis combines stability estimates and consistency estimates to yield optimal-order $H^1$-norm error bounds for the computed surface position, velocity, normal vector, normal velocity and therefore for the mean curvature. The stability analysis is performed in the matrix–vector formulation and is independent of geometric arguments, which only enter the consistency analysis. Numerical experiments are presented to illustrate the convergence results and also to report on monotone quantities, e.g. Hawking mass for inverse mean curvature flow, and complemented by experiments for nonconvex surfaces.
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Error estimates for the Cahn–Hilliard equation with dynamic boundary conditions - Harder, Paula; Kovács, Balázs (IMA Journal of Numerical Analysis)
Abstract A proof of convergence is given for a bulk–surface finite element semidiscretisation of the Cahn–Hilliard equation with Cahn–Hilliard-type dynamic boundary conditions in a smooth domain. The semidiscretisation is studied in an abstract weak formulation as a second-order system. Optimal-order uniform-in-time error estimates are shown in the $L^2$- and $H^1$-norms. The error estimates are based on a consistency and stability analysis. The proof of stability is performed in an abstract framework, based on energy estimates exploiting the anti-symmetric structure of the second-order system. Numerical experiments illustrate the theoretical results.
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Correction to: Stable and convergent fully discrete interior–exterior coupling of Maxwell’s equations - Nick, Jörg; Kovács, Balázs; Lubich, Christian (Numerische Mathematik)
Keywords: Applied Mathematics; Computational Mathematics

A convergent evolving finite element algorithm for Willmore flow of closed surfaces - Kovács, Balázs; Li, Buyang; Lubich, Christian (Numerische Mathematik)
Keywords: Applied Mathematics; Computational Mathematics

Local RBF-based penalized least-squares approximation on the sphere with noisy scattered data - Hesse, Kerstin; Sloan, Ian H.; Womersley, Robert S. (Journal of Computational and Applied Mathematics)
Keywords: Applied Mathematics; Computational Mathematics

Betriebliche Weiterbildungskulturen in Zeiten der Digitalisierung – Eine Analyse mit Daten des BIBB-Qualifizierungspanels. - Krause, Ina; Gerhards, Christian (Internationales Jahrbuch für Erwachsenenbildung 2022: Optimierung in der Weiterbildung)

L-functions of GL(2n): p-adic properties and non-vanishing of twists - Dimitrov, Mladen; Januszewski, Fabian; Raghuram, A. (Compositio Mathematica)
The principal aim of this article is to attach and study $p$ -adic $L$ -functions to cohomological cuspidal automorphic representations $Π$ of $\operatorname {GL}_{2n}$ over a totally real field $F$ admitting a Shalika model. We use a modular symbol approach, along the global lines of the work of Ash and Ginzburg, but our results are more definitive because we draw heavily upon the methods used in the recent and separate works of all three authors. By construction, our $p$ -adic $L$ -functions are distributions on the Galois group of the maximal abelian extension of $F$ unramified outside $p∞$ . Moreover, we work under a weaker Panchishkine-type condition on $Π _p$ rather than the full ordinariness condition. Finally, we prove the so-called Manin relations between the $p$ -adic $L$ -functions at all critical points. This has the striking consequence that, given a unitary $Π$ whose standard $L$ -function admits at least two critical points, and given a prime $p$ such that $Π _p$ is ordinary, the central critical value $L(\frac {1}{2}, Π \otimes χ )$ is non-zero for all except finitely many Dirichlet characters $χ$ of $p$ -power conductor.
Keywords: Algebra and Number Theory

Von ganzen Zahlen zu L-Funktionen - Januszewski, Fabian (Mitteilungen der Deutschen Mathematiker-Vereinigung)
Keywords: Earth-Surface Processes

Excitation of an electronic band structure by a single-photon Fock state - Rose, H.; Vasil'ev, A.N.; Tikhonova, O.V.; Meier, Torsten; Sharapova, Polina R.
In this report, we consider a semiconductor nanostructure in an optical cavity that is coupled to quantum light. We describe the semiconductor nanostructure with a parabolic band structure in a 1D k-space, while we assume a single-mode quantum field. The 1D system is chosen for simplicity in both the analytical and the numerical treatment and paves the way for the description of 2D structures in the future. Therefore, instead of using parameters which are realistic for 1D systems, we rather use parameters which qualitatively correspond to 2D GaAs structures.

Distributed Algorithms for Spectral and Energy-Efficiency Maximization of K-User Interference Channels - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J. (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science

$L^1$ solutions to parabolic Keller-Segel systems involving arbitrary superlinear degradation - Winkler, Michael (ANNALI SCUOLA NORMALE SUPERIORE - CLASSE DI SCIENZE)
Keywords: Mathematics (miscellaneous); Theoretical Computer Science

Is Consistency the Panacea? Inconsistent or Consistent Tax Transfer Prices with Strategic Taxpayer and Tax Authority Behavior - Diller, Markus; Lorenz, Johannes; Schneider, Georg; Sureth-Sloane, Caren

The Tax Complexity Index – A Survey-Based Country Measure of Tax Code and Framework Complexity - Hoppe, Thomas; Schanz, Debora; Sturm, Susann; Sureth-Sloane, Caren
This paper introduces an index that captures the complexity of countries’ corporate income tax systems faced by multinational corporations. It is based on surveys of highly experienced tax consultants of the largest international tax services networks. The index, called the Tax Complexity Index (TCI), is composed of a tax code subindex covering tax regulations and a tax framework subindex covering tax processes and features. For a sample of 100 countries for the year 2016, we find that the level of tax complexity varies considerably across countries, while tax code and framework complexity also vary within countries. From a global perspective, tax complexity is strongly driven by the complexity of both transfer pricing regulations in the tax code and tax audits in the tax framework. When analyzing the associations with other country characteristics, we identify different correlation patterns. For example, tax framework complexity is negatively associated with countries’ governance, suggesting that strongly governed countries tend to have less complex tax frameworks, while tax code complexity is positively associated with the statutory tax rate, indicating that high-tax countries tend to have more complex tax codes. However, none of the observed associa-tions are very strong. We conclude that tax complexity represents a distinct country charac-teristic and propose the use of our TCI and its subindices in future research.

Banks’ tax disclosure, financial secrecy, and tax haven heterogeneitys - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren
This study investigates the effect of mandatory public Country-by-Country Reporting (CbCR) for European banks on their presence in tax and regulatory havens. We find that the number of subsidiaries of European banks in tax havens declines significantly after the introduction of mandatory public CbCR in contrast to insurance firms that need not disclose. We document that this decline is mainly driven by a reduction of subsidiaries in small countries with little economic substance (“dot havens”) and in tax havens that are regulatory havens at the same time, i.e., with high financial secrecy. Further, we find that high exposure to reputational risk is a major amplifier of reorganizational activities. Our results explain prior mixed evidence and document that CbCR effectively curbs tax haven presence only under specific circumstances, i.e., in countries offering both tax shelter and financial secrecy, and more strongly for banks with high reputational risk. These findings suggest that increased tax disclosure on banks does not effectively attenuate tax haven presence per se, but only for a subset of havens and banks. Policymakers need to be aware of these limitations, especially in light of the current decision of extending public CbCR to all large multinationals.

Are Risk-based Tax Audit Strategies Rewarded? An Analysis of Corporate Tax Avoidance - Eberhartinger, Eva; Safaei, Reyhaneh; Sureth-Sloane, Caren; Wu, Yuchen (TRR 266 Accounting for Transparency Working Paper Series No. 60, WU International Taxation Research Paper Series No. 2021-07)

Is Transfer Pricing Harmonization the Panacea? Reporting Transparency, Standards Consistency, and Tax Avoidance - Diller, Markus; Lorenz, Johannes; Schneider, Georg Thomas; Sureth-Sloane, Caren

The Epidemiology of Tax Avoidance Narratives - Lorenz, Johannes; Diller, Markus; Sureth-Sloane, Caren

Spectral Theory of the Frame Flow on Hyperbolic 3-Manifolds - Guillarmou, Colin; Küster, Benjamin (Annales Henri Poincaré)
Keywords: Mathematical Physics; Nuclear and High Energy Physics; Statistical and Nonlinear Physics

Polynomials vanishing at lattice points in a convex set - Gundlach, Fabian (arXiv:2107.05353)
Let $P$ be a bounded convex subset of $\mathbb R^n$ of positive volume. Denote the smallest degree of a polynomial $p(X_1,…,X_n)$ vanishing on $P\cap\mathbb Z^n$ by $r_P$ and denote the smallest number $u≥0$ such that every function on $P\cap\mathbb Z^n$ can be interpolated by a polynomial of degree at most $u$ by $s_P$. We show that the values $(r_{d· P}-1)/d$ and $s_{d· P}/d$ for dilates $d· P$ converge from below to some numbers $v_P,w_P>0$ as $d$ goes to infinity. The limits satisfy $v_P^{n-1}w_P ≤ n!·\operatorname{vol}(P)$. When $P$ is a triangle in the plane, we show equality: $v_Pw_P = 2\operatorname{vol}(P)$. These results are obtained by looking at the set of standard monomials of the vanishing ideal of $d· P\cap\mathbb Z^n$ and by applying the Bernstein--Kushnirenko theorem. Finally, we study irreducible Laurent polynomials that vanish with large multiplicity at a point. This work is inspired by questions about Seshadri constants.

Smaragda Eger-Berg (1886–1954). Bohemienne – Musikerin – Schwester. Bedingungen künstlerischer Emanzipation in der Wiener Moderne - Ricke, Anna

Zwischen "geistig höchststehender Lesbierin" und "verelendeter Geschwitz" – Zur Wahrnehmung der Musikerin Smaragda Eger-Berg (1886-1954) - Ricke, Anna (Musik und Homosexualitäten. Tagungsberichte Bremen 2017 und 2018)

Algorithm-hardware co-design of a discontinuous Galerkin shallow-water model for a dataflow architecture on FPGA - Kenter, Tobias; Shambhu, Adesh; Faghih-Naini, Sara; Aizinger, Vadym (Proceedings of the Platform for Advanced Scientific Computing Conference (PASC))

Share Price Reactions to Tariﬀ Imposition Announcements in the Trump Era – an Event Study of the Trade Conﬂict - Wengerek, Sascha Tobias; Uhde, André
Employing a unique sample of 2,849 tariﬀ imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariﬀ announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariﬀ announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariﬀ impositions, e.g. a decrease in the companies’ future cash ﬂows and a threat of retaliation. The negative wealth eﬀects are observed irrespective of whether the Trump administration announces safeguard tariﬀs to protect domestic ﬁrms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we ﬁnd that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariﬀ, trade and ﬁrm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariﬀs; trade conﬂict

CDS investors’ risk perceptions of M&A announcements - Hippert, Benjamin; Uhde, André
We merge a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across North America and Europe with data from 5-year single-name credit default swaps (CDSs) that are written on stock-listed acquiring firms between 2005 and 2018. Subsequently, we empirically analyze the CDS investors’ risk perception of M&A announcements using event study methodologies. As a baseline finding, we provide evidence for significantly positive cumulative average abnormal CDS spread changes suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design as well as regional and sectoral differences. Moreover, results from a large variety of sensitivity analyses including deal and firm characteristics provide a deeper insight into the driving factors of CDS investors’ risk perceptions of M&A announcements.

Risk allocation through securitization - Evidence from non-performing loans - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
Employing a unique and hand-collected dataset of securitization transactions by European banks, this paper analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios (NPLRs). We provide evidence for an NPLR-reducing effect during the boom phase of securitizations suggesting that banks (partly) securitized NPLs as the most risky junior tranche. In contrast, we find the reverse effect during the crises period indicating that issuing banks demonstrated `skin in the game'. A variety of sensitivity analyses provides further important implications for the vital debate on reducing NPL exposures and regulating securitization markets.
Keywords: European Banking; Non-performing Loans; Risk Allocation; Securitization

‚Wenn die Lehre Kopf steht…‘ Überlegungen zur Gestaltung der Fachdidaktik Wirtschaftswissenschaften auf Basis einer kooperativen Portfolioarbeit - Kückmann, Marie-Ann; H.-Hugo, Kremer; Leonie, Schmid ("Die große Lehre im virtuellen Raum: The Empty Space")

Denken mit dem Stift?! Digitale Visualisierungsprozesse als Zugang zu komplexen wirtschafts- und berufspädagogischen Themenfeldern - Kückmann, Marie-Ann; Kundisch, Heike (bwp@ Berufs- und Wirtschaftspädagogik – online)

Mathematics textbooks and curriculum resources as instruments for change - Rezat, Sebastian; Fan, Lianghuo; Pepin, Birgit (ZDM – Mathematics Education)
Abstract In this survey paper we aim to provide an overview of research on mathematics textbooks and, more broadly, curriculum resources as instruments for change related to mathematical content, instructional goals and practices, and student learning of mathematics. In particular, we elaborate on the following themes: (1) The role of curriculum resources as instruments for change from a theoretical perspective; (2) The design of curriculum resources to mediate the implementation of reform ideas and innovative practice; (3) Teachers’ influence on the implementation of change through curriculum resources; (4) Students’ influence on the implementation of change through curriculum resources; and (5) Evidence of curriculum resources yielding changes in student-related factors or variables. We claim that, whilst textbooks and curriculum resources are influential, they alone cannot change teachers’ teaching nor students’ learning practices in times of curricular change. Moreover, more knowledge is needed about features of curriculum resources that support the implementation of change. We contend that curriculum innovations are likely to be successful, if teachers and students are supported to co- and re-design the relevant curriculum trajectories and materials in line with the reform efforts and their own individual needs.
Keywords: General Mathematics; Education

Challenges of making sense of tasks and automated feedback in digital mathematics textbooks - Rezat, Sebastian; Schacht, Florian; Häsel-Weide, Uta (Mathematics Education in the Digital Age. Learning, Practice and Theory)

How automated feedback from a digital mathematics textbook affects primary students’ conceptual development: two case studies - Rezat, Sebastian (ZDM Mathematics Education)
Abstract One of the most prevalent features of digital mathematics textbooks, compared to traditional ones, is the provision of automated feedback on students’ solutions. Since feedback is regarded as an important factor that influences learning, this is often seen as an affordance of digital mathematics textbooks. While there is a large body of mainly quantitative research on the effectiveness of feedback in general, very little is known about how feedback actually affects students’ individual content specific learning processes and conceptual development. A theoretical framework based on Rabardel’s theory of the instrument and Vergnaud’s theory of conceptual fields is developed to study qualitatively how feedback actually functions in the learning process. This framework was applied in a case study of two elementary school students’ learning processes when working on a probability task from a German 3rd grade digital textbook. The analysis allowed detailed reconstruction of how students made sense of the information provided by the feedback and adjusted their behavior accordingly. This in-depth analysis unveiled that feedback does not necessarily foster conceptual development in the desired way, and a correct solution does not always coincide with conceptual understanding. The results point to some obstacles that students face when working individually on tasks from digital mathematics textbooks with automated feedback, and indicate that feedback needs to be developed in design-based research cycles in order to yield the desired effects.
Keywords: General Mathematics; Education

Fachwissen zur Arithmetik bei Grundschullehramtsstudierenden – Entwicklung im ersten Semester und Veränderungen durch eine Lehrinnovation - Hochmuth, Reinhard; Biehler, Rolf; Blum, Werner; Achmetli, Kay; Rode, Jana; Krawitz, Janina; Schukajlow, Stanislaw; Bender, Peter; Haase, Jürgen (Lehrinnovationen in der Hochschulmathematik . Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Integration digitaler Lernmaterialien in die Präsenzlehre am Beispiel des Mathematikvorkurses für Ingenieure an der Universität Paderborn - Fleischmann, Yael; Biehler, Rolf; Gold, Alexander; Mai, Tobias (Lehrinnovationen in der Hochschulmathematik . Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Die Online-Lernmaterialien im Online-Mathematikvorkurs studiVEMINT: Konzeption und Ergebnisse von Nutzer- und Evaluationsstudien - Gold, Alexander; Fleischmann, Yael; Mai, Tobias; Biehler, Rolf; Kempen, Leander (Lehrinnovationen in der Hochschulmathematik . Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Einführung: Lehrinnovationen in der Hochschulmathematik – praxisrelevant – didaktisch fundiert – forschungsbasiert - Biehler, Rolf; Eichler, Andreas; Hochmuth, Reinhard; Rach, Stefanie; Schaper, Niclas (Lehrinnovationen in der Hochschulmathematik . Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Mathematikvorkurse als Brücke in das Studium–Einführung - Biehler, Rolf (Lehrinnovationen in der Hochschulmathematik . Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)